Foreign Direct Investment in World Economy - Kacperska, Elżbieta (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
Some of the phenomena dynamically developing in global economy in recent years are capital flows in the form of foreign direct investment. The investment takes different forms and is a way of economic development desired by most countries in the world. The article aims to present tendencies occurring in global FDI flows and define their types and geographical structure.